The Role of City Branding in Shaping Policy Strategies and Promoting Inclusivity in the Development of Human Resources for the Creative Economy - Satria Yudha Prakosa; Andreas Okdi Priantoro; Sri Kurnia Abdi Pradhana (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
This study examines the role of city branding as a governance-related instrument in regional development, focusing on its interaction with the creative economy and human capital in shaping inclusive outcomes. Using a qualitative literature review of ten peer-reviewed articles published between 2010 and 2025, the study applies thematic analysis to identify key patterns across the selected literature. The findings suggest that city branding may help align development priorities when supported by strong governance, institutional coordination, and stakeholder participation. The creative economy appears to provide a potential domain for operationalizing branding strategies, while human capital may influence the inclusivity and sustainability of outcomes. However, these relationships are conditional; where governance and policy integration are weak, city branding tends to remain symbolic and fragmented. Given the relatively small and selectively assembled sample of literature, these findings should be interpreted with caution and cannot be readily generalized. The study offers a conceptual synthesis rather than definitive conclusions and highlights the need for further empirical research to validate and refine these relationships.